Transit and Active Transportation Use for Non-Commute Travel Among Portland Transit-Oriented Development Residents. Issue 1 (January 2023) - Dill, Jennifer; McNeil, Nathan
Transit-oriented development (TOD) seeks to promote non-single occupancy vehicle travel by placing dense residential and mixed-use buildings near high-capacity, high-frequency transit. Most research to date on the impact of TODs on travel behavior has focused on commute trips; however, many trips are for non-work purposes, and a sizable portion of the population does not commute to work. This study utilizes a set of surveys, conducted between 2005 and 2019 in the Portland OR region to assess factors associated with whether or not, and how often, TOD residents walk, bike, or take transit for home-based non-work trips. Findings show that about 20% of TOD residents take transit for non-work trips at least once per week, while 65% walk or bike for such trips. Attitudes and housing preferences are important factors in predicting whether and how frequently TOD residents walk, bicycle, or take transit for non-work trips. TOD residents make more non-work trips on transit when there is better transit access, and they walk and bicycle for more of these trips when street connectivity is higher. Lower access to a personal vehicle is also an important factor in non-work travel.